The Effect of Providing Regional Infrastructure on Economic Growth in Gunung Mas District - Asri Alie; Sunaryo Neneng; Luluk Tri Harinie (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2019)
This study aims to analyze the influence of the availability of regional infrastructure which isfocused on road infrastructure, electricity infrastructure, education infrastructure, and healthinfrastructure towards economic growth in Gunung Mas District. This research method isquantitative by using secondary time series data from 2000-2017. Data were analyzed usingmultiple linear regression analysis. The results showed that partially variables roadinfrastructure, electricity infrastructure, and education infrastructure had a positive andsignificant effect on economic growth, except health infrastructure that did not affecteconomic growth. Simultaneously the independent variables have a positive and significanteffect on economic growth. The value of R square is 0.743 which means that 74.3 percent ofinfrastructure variables are able to explain economic growth in Gunung Mas Regency